Core epitope analysis of 16 kDa allergen from tartary buckwheat. (1st June 2021) - Zheng, Bei; Zhang, Haina; Shen, Wei; Wang, Lei; Chen, Peng
Highlights: Six B-cell and seven T cell epitopes of Fag t 2 were predicted by bioinformatics method. The amino acids 52, 87, 100, and 132 played a role in allergenicity of Fag t 2. The ENQKGRIGET and KCGISEMECH peptide were the T cell core epitopes of Fag t 2. Abstract: Tartary buckwheat is widely accepted as its nutritional value. Some allergic reactions hinder its utilization. This research focused on evaluating the core epitope of 16 kDa allergen (Fag t 2) in tartary buckwheat. Six B- and seven T cell epitopes of Fag t 2 were predicted, and six B cell epitope-mutants were expressed in Pichia pastoris . Bioinformatics analysis and SDS-PAGE demonstrated that the molecular weight, isoelectric point and spatial structures of six mutant allergens were similar with Fag t 2, with the same signal peptide sequences and α-amylase inhibitor domain. There was no significant change in mutants' spatial conformation confirmed by Circular Dichroism. The position K132N and peptides at 108–117 and 132–141 were the core B- and T cell epitopes of Fag t 2 confirmed by competitive inhibition ELISA and dot blot. This result was of great significance on the study of allergen epitopes in prevention and treatment of hypersensitivity.